End-of-life management strategies of pharmaceuticals in Portuguese households. Issue 1 (January 2023) - Veiga, Anabela; Sousa, Ana Catarina; Sousa, Cláudia; Oliveira, Manuel; Neto, Belmira
The end of life of pharmaceutical products through environmentally unsafe routes is a growing concern in our society. However, the studies reported so far, apart from being limited in number, do not reflect the current management practices for the end-of-life management of pharmaceuticals. Published work lacks an in-depth analysis in focusing on the pharmaceutical waste in households. The present work focused on (1) performing a state-of-the art overview to compare worldwide studies and the results and (2) implementing a comprehensive survey in Portugal ( n  = 454 respondents). The results showed that the delivery to pharmacies was used by the majority of the respondents (72%), indicating a good awareness of pharmaceutical waste management issues, when compared to the reviewed studies. Statistically significant variables for the destination of end-of-use pharmaceuticals include gender, age and distance from the residence to the pharmacy ( p  < 0.05). Most participants believe that educating the population on existing structures of medication and packaging management is of the utmost importance to improve the national managing system. This is the first study conducted in Portugal; it includes statistical analysis of the data and reflects on the practices that should be adopted to reduce incorrect pharmaceutical waste disposal. These findings call upon the strategies to strengthen the pharmaceutical waste management programme.